Production of extracellular vesicles with light‐induced proton pump activity by proteorhodopsin‐containing marine bacteria - Yong Min Kwon (MicrobiologyOpen, 2019)
Abstract The production and release of extracellular vesicles (EVs) is a common process occurring in various types of bacteria. However, little is known regarding the functions of EVs derived from marine bacteria. We observed that during cell growth, Sediminicola sp. YIK13, a proteorhodopsin (PR)‐containing marine flavobacterium, produces EVs (S13EVs). Transmission electron microscopy showed that Sediminicola sp. YIK13 released two spherical vesicle types, with mono‐ and/or bi‐layered membranes, in the culture. Interestingly, the S13EVs have an orange pigment, indicating the presence of putative carotenoid and PR pigments ascribed to the parental cells. The S13EVs demonstrated the same PR‐derived absorption peak spectrum and light‐induced proton pump activity as the parental cells. Western blot (immunoblot) analysis of the S13EVs revealed the presence of PR. We confirmed the 16S rRNA gene, pro gene, and genes required for chromophore retinal synthesis, namely blh and crtI, in the DNA packaged into these vesicles. In addition, by metagenomic sequencing, we found microbial rhodopsin‐related genes in vesicles derived from natural aquatic environments. Our results suggest that EVs as well potentially pursue horizontal gene transfer of diverse microbial rhodopsin genes in marine ecosystems.